UNESCO Global Geoparks Indonesia in Online Space : A Review of Tourism Information Availability - Setiawan, Deddy (Avant Garde, 2024)
ABSTRACT Geoparks are modern geotourism products that open up new opportunities and ways of presenting geological heritage. Promotion and marketing of geoparks is still minimal, and needs to be improved. That is why it is necessary to investigate this area, the purpose of this study explores the tourism information provided from analyzing the complexity of the UNESCO Global Geopark website in Indonesia. The research method was a survey of the websites of 10 UNESCO Global Geoparks in Indonesia which then tried to categorize general information about the values of geoparks and gradually moved to groups of important tourism information from the point of view of researchers who were placed as visitors to visit geoparks. This research resulted in the answer that UNESCO Global Geopark Indonesia is at the classic marketing level with low or passive activity on its website. In addition, the geopark has understood the importance of social media marketing is a positive thing, but the level of activity in this area is not yet entirely adequate.